Strangers and Necropolitics in NoViolet Bulawayo’s We Need New Names - Suárez-Rodríguez, Ángela (International Journal of English Studies, 2022)
As a contribution to the recent call for the study of the figure of the stranger in African spaces (Ikhane, 2020), this article examines the first half of NoViolet Bulawayo’s We Need New Names (2013). The main reason for this, it is argued, is that the description of the protagonist’s pre-migratory living conditions throughout this part of the narrative reveals a Zimbabwean nation in which the necropolitics resulting from the failures of decolonisation have turned certain segments of the population into strangers in their own land. Their “living dead” status in a situation of social and spatial marginalisation recalls, in particular, the notion of the stranger as the “socially dead” (Rothe & Collins, 2016). However, unlike this and other classical strangers living in a Western urban context, the literary strangers studied here do not represent an othered minority in the community but, rather, exemplify what appears to be a widely shared condition of “strangerness” in some contemporary African cities.